Japanese and American agriculture: Tradition and progress in conflict (Westview Press, 1993)
Despite vast differences in culture, farm structure, food consumption, and farm and food policy between the United States and Japan, economic progress has brought about strikingly similar structural changes in American and Japanese agriculture. American policies have tended to emphasize outmigration and farm enlargement, and Japanese approaches have tended to emphasize part-time farming, but both approaches have proven extremely costly and have failed to preserve rural traditions and institutions. neither country likes what economic progress has done to its farm structure.